Synthesized nanocomposite TiN/a-SiNx films - PHINICHKA, Natthapong; CHANDRA, Ramesh; BARBER, Zoe H. (Journal of Metals, Materials and Minerals, 2022)
Nanocomposite hard coatings, nc-TiN/a-SiNx, were synthesized by an ionized magnetron sputter deposition technique (IMSD). The maximum hardness of 40.06 GPa, approximately double that of TiN, is reached at Ti0.88:Si0.12 with an rf power of 100 W and negative bias of 150 V. The hardness of the films was measured using nanoindentation. At an applied load of less than 70 mN, the indentation depth is less than 10% of the film thickness and the results show no effect of substrate on the hardness of the films. The effects of ion flux and energetic bombardment on the properties of the films were observed by varying the rf power to the built-in rf coil where an inductively coupled plasma is generated, and the dc substrate bias of which the bombardment energy is controlled. X-ray diffraction was used to investigate the structure and grain size, and its correlation with hardness behavior as a function of Si content and bias voltage. Only one phase that can be assigned to TiN was found. No signals from crystalline Si3N4 or other phases of titanium silicide were observed. The preferential growth, as a function of Si content and bias voltage, changes from (111) to a preferred (200) orientation when negative bias voltage and Si content is increased. For high hardness films, the nanocrystallite domain size of the TiN, calculated from peak broadening, was found to be less than 10 nm.